The Sangamonian Pointe-Fortune Site, Ontario-Québec Border - Anderson, Thane; Matthews, John; Mott, Robert; Richard, S. (Géographie physique et Quaternaire, 1990)
ABSTRACTInter-till sediments (Units 2, 3, 4) in a sand pit located 115 km east of Ottawa, Ontario, contain a predominance of deciduous tree pollen including oak. elm, beech and hickory {Quercus, Ulmus, Fagus, and Carya) and minor amounts of basswood, ash and sweetgum (TiHa, Fraxinus and Liquidambar). Unit 4 also contains macrofossils of several plant taxa which presently do not grow much north of the site. The fossils portray an inter-glacial environment (the Sangamonian) with conditions as warm as or warmer than the present in the area. By contrast, overlying Unit 4a reveals a dominance of boreal indicators such as pollen of spruce, pine, willow and alder (Picea, Pinus, Salix and Alnus) and the beetles, Bembidion transparens, Eucnecosum, and Olophrum boréale. Unit 4a fossils indicate a climate that was colder than at present but no colder than the climate of central Québec - suggesting a correlation with the waning phase of the warm interval, or alternatively, with the St. Pierre Interstade of the St. Lawrence Lowlands. Thus the lower till is interpreted as lllinoian in age; the upper till may be Middle to Late Wisconsinan or Early to Late Wisconsinan.